Psoralen-loaded lipid-polymer hybrid nanoparticles enhance doxorubicin efficacy in multidrug-resistant HepG2 cells - Yuan Y (Dove Medical Press, 2019)
Yueling Yuan,1,* Tiange Cai,2,* Richard Callaghan,3,* Qianwen Li,4 Yinghong Huang,4 Bingyue Wang,1 Qingqing Huang,1 Manling Du,1 Qianqian Ma,1 Peter Chiba,5 Yu Cai1,6 1College of Pharmacy, Jinan University, Guangzhou, Guangdong 510632, China; 2College of Life Science, Liaoning University, Shenyang, Liaoning 110000, China; 3Research School of Biology, Australian National University, Canberra ACT 2601, Australia; 4Guangzhou Guoyu Pharmaceutical Technology Co., Ltd., Guangzhou, Guangdong 510663, China; 5Institute of Medical Chemistry, Medical University of Vienna, Vienna 1090, Austria; 6Cancer Research Institute, Jinan University, Guangzhou, Guangdong 510632, China *These authors contributed equally to this work Background: Psoralen (PSO), a major active component of Psoralea corylifolia, has been shown to overcome multidrug resistance in cancer. A drug carrier comprising a lipid-monolayer shell and a biodegradable polymer core for sustained delivery and improved efficacy of drug have exhibited great potential in efficient treatment of cancers.Methods: The PSO-loaded lipid polymer hybrid nanoparticles were prepared and characterized. In vitro cytotoxicity assay, cellular uptake, cell cycle analysis, detection of ROS level and mitochondrial membrane potential (ΔΨm) and western blot were performed. Results: The P-LPNs enhanced the cytotoxicity of doxorubicin (DOX) 17-fold compared to free DOX in multidrug resistant HepG2/ADR cells. Moreover, P-LPNs displayed pro-apoptotic activity, increased levels of ROS and depolarization of ΔΨm. In addition, there were no significant effects on cellular uptake of DOX, cell cycle arrest, or the expression of P-glycoprotein. Mechanistic studies suggested that P-LPNs enhanced DOX cytotoxicity by increased release of cytochrome c and enhanced caspase3 cleavage, causing apoptosis in HepG2/ADR cells.Conclusion: The lipid-polymer hybrid nanoparticles can be considered a powerful and promising drug delivery system for effective cancer chemotherapy. Keywords: lipid-polymer hybrid nanoparticles, psoralen, drug delivery, HepG2, ADR cells, apoptosis